(untitled) (Journal of Advanced Veterinary and Animal Research, 2025)
Recent studies have identified wing cells, a substructure of the wing, as carrying taxonomic signals across various mosquito genera. However, the presence of a taxonomic signal in the wing cells of the genus Lutzia (Diptera: Culicidae) has not yet been confirmed. Objective: This study aimed to evaluate the efficacy of the outline-based geometric morphometric (GM) approach in distinguishing Lutzia species found in Thailand, namely Lutzia chiangmaiensis, Lutzia fuscana, Lutzia halifaxii, and Lutzia vorax. Materials and Methods: The outline-based geometric morphometrics was employed to analyze four wing elements: the wing contour, the second submarginal cell, the first posterior cell, and the third posterior cell. Results: In the size analysis, Lt. vorax consistently exhibited significantly larger wing elements compared to the other species (p < 0.05). The factor maps based on discriminant analysis for the wing elements among the species indicated that most groups overlapped in morphospace. However, for the third posterior cell, the Lt. vorax group presented a more distinct shape. While shape analysis detected significant differences between almost all species pairs (p < 0.05), there was an exception between Lt. halifaxii and Lt. chiangmaiensis in the first posterior cell (p > 0.05). Additionally, shape analysis further indicated that the third posterior cell achieved the highest percentage of correct classifications, with an adjusted total assignment accuracy of 71%. Conclusion: This finding reveals a significant taxonomic signal in the third posterior cell, suggesting that the outline-based GM approach can effectively complement the landmark-based GM approach in distinguishing Lutzia species. J. Adv. Vet. Anim. Res., 12(2): 516–528, June 2025 http://doi.org/10.5455/javar.2025.l916